Infliximab therapy intensification based on endoscopic activity is related to suppress treatment discontinuation in patients with Crohn disease: A retrospective cohort study. Issue 6 (12th February 2021) - Komaki, Yuga; Kanmura, Shuji; Yutsudo, Kazuki; Kuwazuru, Kosuke; Komaki, Fukiko; Tanaka, Akihito; Nishimata, Nobuaki; Sameshima, Yoichi; Sasaki, Fumisato; Ohi, Hidehisa; Nakamura, Yuichi; Tokushige, Koichi; et al.
Abstract : Abstract: Administering double doses of infliximab or shortening its dosing interval for patients with Crohn disease who experience a loss of response to treatment is an accepted treatment method; however, the effectiveness and appropriate timing of treatment intensification remain unclear. We examined the treatment outcomes of patients with Crohn disease receiving infliximab therapy intensification. Among 430 patients with Crohn disease who were seen at our related facilities from July 2002 to July 2018, 46 patients (30 men and 16 women) who were followed up for diminished infliximab effects for >1 year after therapy intensification were included in this study. The relationship between patient background and continuation of therapy intensification was retrospectively examined through a logistic regression analysis. Among the 46 patients, 67.4% (31 cases) continued therapy intensification for 12 months. The treatment discontinuation rate after 12 months (7.1% vs 43.8%, P = .015) and the C-reactive protein levels at the start of therapy intensification ( P = .0050) were significantly lower in the group in which treatment was strengthened due to remaining endoscopic findings (n = 14) than that due to clinical symptoms (n = 32). There was no significant difference in the rates of treatment discontinuation after 12 months of treatment strengthening between patients receiving double doses (n = 34) and those with shortened dosing intervals (n = 12). Infliximab treatment discontinuation seems to be less likely to occur in patients with Crohn disease who are receiving infliximab treatment intensification based on endoscopic findings of exacerbations than in patients whose treatment is based on clinical symptoms.